1990
DOI: 10.1128/mcb.10.6.2678-2686.1990
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression of cDNA for a Human Low-Km, Rolipram-Sensitive Cyclic AMP Phosphodiesterase

Abstract: We have isolated cDNA clones representing cyclic AMP (cAMP)-specific phosphodiesterases (PDEases) from a human monocyte cDNA library. One cDNA clone (hPDE-1) defines a large open reading frame of ca. 2.1 kilobases, predicting a 686-amino-acid, ca. 77-kilodalton protein which contains significant homology to both rat brain and Drosophila cAMP PDEases, especially within an internal conserved domain of ca. 270 residues. Amino acid sequence divergence exists at the NH2 terminus and also within a 40- to 100-residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…The effective therapeutic concentrations of rolipram in vivo are, however, very similar to the apparent K d of the observed high-affinity (R)-rolipram binding and not to the apparent K i of enzyme inhibition (Bolger et al, 1993). Previous studies using (R)rolipram revealed that some Type 4 PDE enzyme preparations exhibit a competitive inhibition pattern suggesting inhibition at the catalytic site (Nemoz et al, 1989;Livi et al, 1990), whereas other enzyme preparations have complex inhibitory kinetics (Torphy et al, 1992;Bolger et al, 1993;McLaughlin et al, 1993;Amegadzie et al, 1995), suggesting the presence of multiple binding forms of PDE. To determine whether PDE 4 has an intrinsic high-affinity for rolipram, Torphy et al (1992) expressed a human recombinant monocytic Type 4 PDE in yeast cells and determined that high-affinity rolipram binding and cAMP turnover were coexpressed.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…The effective therapeutic concentrations of rolipram in vivo are, however, very similar to the apparent K d of the observed high-affinity (R)-rolipram binding and not to the apparent K i of enzyme inhibition (Bolger et al, 1993). Previous studies using (R)rolipram revealed that some Type 4 PDE enzyme preparations exhibit a competitive inhibition pattern suggesting inhibition at the catalytic site (Nemoz et al, 1989;Livi et al, 1990), whereas other enzyme preparations have complex inhibitory kinetics (Torphy et al, 1992;Bolger et al, 1993;McLaughlin et al, 1993;Amegadzie et al, 1995), suggesting the presence of multiple binding forms of PDE. To determine whether PDE 4 has an intrinsic high-affinity for rolipram, Torphy et al (1992) expressed a human recombinant monocytic Type 4 PDE in yeast cells and determined that high-affinity rolipram binding and cAMP turnover were coexpressed.…”
mentioning
confidence: 56%
“…Two Type 4 phosphodiesterases, HSPDE4A and HSPDE4B2B, have been cloned from human brain and expressed in recombinant systems (McLaughlin et al, 1993;Livi et al, 1990). Data from these studies suggest that these proteins contain a high-affinity (R)-rolipram binding site that may represent an allosteric site or one of two distinct catalytic forms of the protein molecule (Torphy et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report of a recombinant PDE to be purified from bacteria and obtained in relatively large quantities [although PDE4D1 has been expressed before as a nonfusion protein in E. coli (Swinnen et al, 1989b;Jin et al, 1992) and many PDE4s have been expressed in eukaryotic cells, e.g. Livi et al (1990), Torphy et al (1992), Bates et al (1993), Bolger et al (1993), and Monaco et al (1994)].…”
Section: Discussionmentioning
confidence: 99%
“…Since PDE4 inhibitors act on inflammatory processes, mainly on oxygen-derived free radicals [16], and that moreover some failures (unsolved mortality) were obtained during the PDE3 inhibitor development, PDE4 research was preferentially developed. In another way, the cloning and expression of cDNA for a human low-K m , rolipram-sensitive cAMP phosphodiesterase was firstly reported in 1990 [17] as well as the structure of two rat genes coding for rolipram-sensitive cAMP-PDE [18]. Thus, pharmaceutical companies have conducted many studies to design and develop increasingly potent and specific PDE4 inhibitors (for review see: Houslay et al, 2005 [19].…”
Section: The Pde4 Familymentioning
confidence: 99%